2021
DOI: 10.3390/v13112224
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL Reduces Chinese Giant Salamander Iridovirus-Induced Mitochondrial Apoptosis by Interacting with Bak and Inhibiting the p53 Pathway

Abstract: Chinese giant salamander iridovirus (GSIV) infection could lead to mitochondrial apoptosis in this animal, a process that involves B-cell lymphoma-2 (BCL-2) superfamily molecules. The mRNA expression level of Bcl-xL, a crucial antiapoptotic molecule in the BCL-2 family, was reduced in early infection and increased in late infection. However, the molecular mechanism remains unknown. In this study, the function and regulatory mechanisms of Chinese giant salamander (Andrias davidianus) Bcl-xL (AdBcl-xL) during GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that p53 signaling is a crucial pathway that participates in the regulation of the apoptotic signaling cascade, which has been shown to be a direct transcriptional activator of Bax/Bak ( 9 ). ( 65 ) revealed that the protein level of p53 increased during Chinese giant salamander iridovirus (GSIV)-induced apoptosis in Andrias davidianus and that the anti-apoptotic molecule AdBcl-xL inhibited the anti-apoptotic effect of p53. Therefore, our results suggest that the anti-apoptotic activity of TroBcl2 may be related to inhibition of p53 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that p53 signaling is a crucial pathway that participates in the regulation of the apoptotic signaling cascade, which has been shown to be a direct transcriptional activator of Bax/Bak ( 9 ). ( 65 ) revealed that the protein level of p53 increased during Chinese giant salamander iridovirus (GSIV)-induced apoptosis in Andrias davidianus and that the anti-apoptotic molecule AdBcl-xL inhibited the anti-apoptotic effect of p53. Therefore, our results suggest that the anti-apoptotic activity of TroBcl2 may be related to inhibition of p53 activation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Chinese giant salamander iridovirus (GSIV) infection inhibits the expression of AdBcl-xL [ 53 ], and overexpression suppresses virus replication. Furthermore, AdBcl-xL inhibits the mitochondrial apoptotic cell death induced by GSIV by binding to Bak, which reduces caspase-3 and caspase-9 activation.…”
Section: Discussionmentioning
confidence: 99%
“…He et al (2019) postulate that the mitochondrial localization of TFV vBcl-2 suggests a role in the direct inhibition of intrinsic apoptosis [ 66 ]. Chinese giant salamander ( Andrias davidianus ) iridovirus (GSIV) has been shown to regulate apoptosis in vitro, with GSIV promoting both intrinsic and extrinsic pathways of apoptosis in infected cells [ 67 ], with further in vitro studies by Li et al (2021) showing that the Chinese giant salamander Bcl-x L was capable of limiting GSIV infection when overexpressed in cultured giant salamander muscle cells [ 68 ].…”
Section: Viral Bcl-2 Genes and The Regulation Of Apoptosismentioning
confidence: 99%